Naming names: the first women taxonomists in mycology - Maroske, Sara (Stud Mycol, 2018)
The transition from amateur to professional in natural history is generally regarded as having taken place in the nineteenth century, but landmark events such as the 1917 appointment of mycologist Johanna Westerdijk (1883–1961) as the first female professor in the Netherlands indicate that the pattern of change for women was more varied and delayed than for men. We investigate this transition in mycology, and identify only 43 women in the Western World who published scientific mycological literature pre-1900, of whom twelve published new fungal taxa. By charting the emergence of these women over time, and comparing the output of self-taught amateurs and university graduates, we establish the key role of access to higher education in female participation in mycology. Using a suite of strategies, six of the self-taught amateurs managed to overcome their educational disadvantages and name names — Catharina Dörrien (the first to name a fungal taxon), Marie-Anne Libert, Mary Elizabeth Banning, Élise-Caroline Bommer, Mariette Rousseau, and Annie Lorrain Smith. By 1900, the professional era for women in mycology was underway, and increasing numbers published new taxa. Parity with male colleagues in recognition and promotion, however, remains an ongoing issue.